Pengaruh Jumlah Sudu Terhadap Efisiensi Turbin Angin Savonius Sumbu Vertikal - Niharman Niharman; Een Tonadi; Bobby Raditya Ardana (MAJALAH TEKNIK SIMES, 2021)
One of the potential new and renewable energy sources is wind energy. Wind energy is a clean energy source with no emissions. The government is quite concerned about reducing the use of fossil energy sources and switching to renewable energy that is more friendly to the environment and has unlimited sources. for example in 2025 the government targets the installed capacity for wind energy to be 0.97 GW. For that we need a continuous study of the potential utilization of wind energy. The purpose of this study was to determine the effect of the number of blades on the efficiency of the vertical axis savonius turbine. The test was carried out with 3 variations in the number of blades, namely with 3 blades, 6 blades and 12 blades at a wind speed of 3.5 m / s. To drive the turbine, a fan is installed at a distance of 500 mm from the turbine. The results showed that the highest efficiency was owned by the turbine with the number of blades 12 at a wind speed of 3.5 m / s, namely 23% with a generator output power of 1.94 watts, 398.8 rpm rotation, 0.046 torque. The smallest efficiency was obtained in the 3 blade test, which was 4.2%. Then the research can be concluded that the number of blades greatly affects the value of efficiency, it can be seen that the number of blades 12 get a greater efficiency value than the number of blades 3 and 6.